Agrotourism: A Catalyst for Rural Revitalization and Sustainable Tourism in Nigeria - Olagunju, Oluwatoyin Olatunde (East Asian Journal of Multidisciplinary Research, 2024)
Agrotourism in Nigeria has shown to be a workable strategy for both rural rehabilitation and sustainable tourism expansion. This study examines how agrotourism might support environmentally conscious travel practices and assist rural communities in addressing socio-economic challenges. Using empirical data and previous research, the paper examines the key components of agrotourism in the Nigerian setting, including farm stays, agritourism activities, and culinary tourism. The report emphasizes how important agrotourism is to diversifying the rural economy, generating jobs, and enhancing residents' quality of life.  Agrotourism projects can raise rural incomes, lower poverty, and stop the movement of people from rural to urban areas by utilizing Nigeria's rich agricultural legacy and cultural variety. Agrotourism also encourages community involvement, cultural interaction, and the preservation of customs, all of which support rural communities' sustainable development.